2014
DOI: 10.1016/j.metabol.2014.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and environmental determinants of the susceptibility of Amerindian derived populations for having hypertriglyceridemia

Abstract: Here, we discuss potential explanations for the higher prevalence of hypertriglyceridemia in populations with an Amerindian background. Although environmental factors are the triggers, the search for the ethnic related factors that explains the increased susceptibility of the Amerindians is a promising area for research. The study of the genetics of hypertriglyceridemia in Hispanic populations faces several challenges. Ethnicity could be a major confounding variable to prove genetic associations. Despite that,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 38 publications
(42 reference statements)
4
25
0
Order By: Relevance
“…We performed a cis -eQTL analysis for the 5 genes within this TG-associated LD block using adipose RNA-seq samples (n=795) from the METSIM cohort and discovered that the lead SNP rs9949617 (i.e. the SNP with the strongest TG association signal 4 ) and its LD proxies are a cis -eQTL, regulating the expression of one regional gene, the transmembrane protein 241 ( TMEM241 ) (p=6.11x10 −07 –5.80x10 −04 ) (table 1). These results pass the Bonferroni correction for the 50 performed tests (10 SNPs tested for 5 regional genes; p<0.001) (table 1), and the 10 TG-associated SNPs did not regulate expression of any of the 4 other genes within the LD block (Bonferroni corrected p>0.05).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We performed a cis -eQTL analysis for the 5 genes within this TG-associated LD block using adipose RNA-seq samples (n=795) from the METSIM cohort and discovered that the lead SNP rs9949617 (i.e. the SNP with the strongest TG association signal 4 ) and its LD proxies are a cis -eQTL, regulating the expression of one regional gene, the transmembrane protein 241 ( TMEM241 ) (p=6.11x10 −07 –5.80x10 −04 ) (table 1). These results pass the Bonferroni correction for the 50 performed tests (10 SNPs tested for 5 regional genes; p<0.001) (table 1), and the 10 TG-associated SNPs did not regulate expression of any of the 4 other genes within the LD block (Bonferroni corrected p>0.05).…”
Section: Resultsmentioning
confidence: 99%
“…According to a recent survey, both the U.S. Hispanic men and women have higher levels of serum TGs than non-Hispanic whites or blacks 3 , a result consistently reported for the last two decades 4 . Recent studies utilizing Latino cohorts have successfully narrowed European lipid loci 5 .…”
Section: Introductionmentioning
confidence: 81%
“…It has been observed that hypertriglyceridemia is more frequent in adults who live in metropolitan areas or in the central region of the country, without any influence being shown by educational level or socioeconomic status. It is well known that Hispanics have greater susceptibility to have hypertriglyceridemia 9 . For example, in the United States, the Hispanic population has a higher prevalence of hypertriglyceridemia (40.4% for men and 31.6% for women) compared to Caucasians and African-Americans.…”
Section: Epidemiology Of Dyslipidemias In Mexicomentioning
confidence: 99%
“…For example, using novel lipid traits or underrepresented populations and allowing for pleiotropic effects have successfully identified novel loci [18,23,24▪,2527]. Often, the most highly associated SNVs do not have a direct effect, but mark a region containing causal variation.…”
Section: Statistical Genetics Approaches To Complex Traitsmentioning
confidence: 99%